A comparative study of conventional periodontal therapy and modified keyes method - Galang, Gregoria Irmina A.; Sia Su, Mary Judy L.
This study attempted to compare the clinical results of conventional periodontal therapy and modified Keyes Technique. Ten subjects with gingival index scores of 2 where selected for the study. Upper and lower arches were divided into right and left halves with emphasis on all anterior teeth. The left side was treated with scaling, root planing, subgingival curettage and daily irrigation with warm saturated salt solution supplemented with a home case plaque control regimen (Modified Keyes Method). The controlateral half was designated as the control site there only scaling, root planing & subgingival curettage and home care plaque control was instituted. The 4 variables evaluated in both test and control sites were the oral hygiene status, gingival condition, number of sites which blad upon probing and depth of the pockets. Subjects were monitored after 7 and 14 days. The final measurements were compared with the initial measurements of determine any changes that occurred with instrumentation and adjuncts employed. No significant difference between experimental and control subgroups were found in all 4 variables. It was the clinical observation that with or without the adjunct these was a general improvement of the gingival conditions of the patients.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Periodontal diseases -- Therapy -- Methods; Periodontics